α-Synuclein Aggregates and Parkinson's disease - Oliveira, Isadora Cucolo; Santos, Tárik Abdalla dos; Covizzi, Ian Vilas Boas; Scalon, Thatiana; Bôas, João Renato Villas; Andrade, Frans Eberth Costa; Lima, Alba Regina de Abreu; Vayego, Sheila Adami; Covizzi, Uderlei Doniseti Silveira (Seven Editora, 2024)
Parkinson's disease (PD) is characterized by the progressive degeneration of dopaminergic neurons of the substantia nigra, leading to motor changes that progress to tremors, rigidity, and bradykinesia with postural instability. Over time, cognitive disorders such as mild dementia, emotional changes such as depression and anxiety, autonomic and sleep disorders are observed. It is the second most prevalent neurodegenerative disease among the elderly population, and is a chronic and progressive clinical condition. It is currently classified as a synucleinopathy, belonging to a group of diseases characterized by anomalous deposition of the alpha-synuclein protein. This protein aggregates abnormally in neuronal tissue, giving rise to Lewy bodies. α-synuclein is a soluble protein of 140 amino acids that appears abundantly in the synaptic terminals of neurons. The sequence of terminal N amino acids from 1-60 is composed of several lysines and these repeats appear to be important for interaction with vesicle lipids. The central sequence that surrounds the amino acid residues 61-95 is the most hydrophobic portion of the protein, being known as the non-amyloid beta component, capable of changing its state from helix to pleated beta sheet, exposing the hydrophobic groups and favoring protein aggregation. The 96-140 residues of the terminal C are mainly made up of acidic, negatively charged amino acids, which are necessary for calcium binding. The pathogenic mechanisms of PD involve incorrect folding and aggregation of α-synuclein, failure of the metabolism of these proteins due to deficiency in the proteosome/ubiquitin or phagolysomal system, mitochondrial dysfunction, inflammation, and oxidative stress. Most cases of Parkinson's are characterized by being sporadic in nature, corresponding to about 90-95%. The monogenic forms may be recessive or dominant, consisting of only 30% of familial cases and accounting for only 3-5% of sporadic cases. DOI:https://doi.org/10.56238/sevened2024.001-055